A Study: UML for OOA and OOD - Rajagopal, D.; Thilakavalli, K. (International Journal of Knowledge Content Development & Technology, 2017)
The notion of object oriented analysis and design in software engineering has many rewards that aid the programmer to have an understanding of and improve the program efficaciously. Object oriented metrics helps rather a lot to a programmer or developer to comprehend and unravel the thing-oriented trouble readily and exactly. Object oriented metrics helps in examining the usefulness of object oriented applied sciences or in simple phrases Object-oriented metrics depict characteristics of object-oriented programming. The intention of this paper is to have an understanding of concerning the UML, Object oriented evaluation and design and the way it plays in UML. URL: http://ijkcdt.net/xml/10969/10969.pdf